Thrombin/PAR-1 activation induces endothelial damages via NLRP1 inflammasome in gestational diabetes - Liu, Yue; Tang, Zhuang-Zhuang; Zhang, Yu-Meng; Kong, Li; Xiao, Wei-Fen; Ma, Teng-Fei; Liu, Yao-Wu (Biochemical pharmacology, 2020)
[Display omitted] Gestational diabetes mellitus (GDM) is associated with an increased risk of progressing to type 2 DM and cardiovascular disease; however, the pathogenesis is still poorly understood. This study was to investigate roles of thrombin and its receptor protease-activated receptor 1 (PAR-1) and NLRP1 inflammasome in endothelial injury in GDM condition. Umbilical cord and plasma of GDM patients and high glucose (HG) cultured human umbilical vein endothelial cells (HUVECs) were used to examine the pathological changes of these pathways. Meanwhile, ameliorative effects and potential mechanisms of a natural product sarsasapogenin (Sar) were investigated in HUVECs. Thrombin/PAR-1 pathway, advanced glycation endproducts (AGEs) and their receptor (RAGE) axis, and the nucleotide-binding domain and leucine-rich repeat containing protein 1 (NLRP1) inflammasome were activated in GDM condition and HG-cultured HUVECs, accompanied by endothelial injury (decreased cell viability and increased lactate dehydrogenase release). Nevertheless, thrombin inhibition or PAR-1 antagonism caused decreases in AGEs formation and RAGE expression in HG-cultured HUVECs, while AGEs inhibition or RAGE antagonism declined PAR-1 expression not thrombin activity. Furthermore, thrombin inhibition or PAR-1 antagonism restrained NLRP1 inflammasome activation in HG-cultured HUVECs; meanwhile, NLRP1 expression and interleukin 18 levels were remarkably reduced in HG-cultured HUVECs after PAR-1 knockdown. Interestingly, Sar co-treatment could suppress thrombin/PAR-1 pathway, NLRP1 inflammasome, and AGEs/RAGE axis. Together, endothelial damages in GDM were likely due to enhanced interaction between AGEs/RAGE axis and thrombin/PAR-1 pathway, followed by NLRP1 inflammasome activation. Moreover, Sar may act as a protective agent against endothelial injury in chronic HG condition.